Sapiens : a graphic history. The birth of humankind. Volume one - Harari, Yuval N.; Vandermeulen, David, 1968-; Casanave, Daniel (New York : Harper Perennial, 2020)
In this first volume of the full-color illustrated adaptation of his groundbreaking book, renowned historian Yuval Harari tells the story of humankind's creation and evolution, exploring the ways in which biology and history have defined us and enhanced our understanding of what it means to be 'human'. From examining the role evolving humans have played in the global ecosystem to charting the rise of empires, Sapiens challenges us to reconsider accepted beliefs, connect past developments with contemporary concerns, and view specific events within the context of larger ideas.
Graphic novel adaptation of: Sapiens : a brief history of humankind by Yuval N. Harari.
First published in Hebrew in 2011 by Kinneret, Zmora-Bitan, Dvir.
Translated from the French (original work in Hebrew)
Keywords: Civilization -- History -- Comic books, strips, etc; Human beings -- History -- Comic books, strips, etc; World history -- Comic books, strips, etc; Chronology, Historical -- Comic books, strips, etc; Technology and civilization -- History -- Comic books, strips, etc